"An Amorphous Code": The Ku Klux Klan and Un-Americanism, 1915–1965. (November 2013) - LEWIS, GEORGE
<x content-type="archive" xml:space="preserve">Abstract</x> On 1 June 1965, the House Un-American Activities Committee (HUAC) announced that it would hold hearings into the Ku Klux Klan, fifty years after the organization had appeared before the House Rules Committee. Whereas the 1925 investigation allowed the Klan to continue to claim a "100% Americanism, " HUAC unequivocally declared the Klan of the 1960s to be entirely un-American. This essay seeks to explain that turnaround in the understanding of the Klan and its activities, on the one hand, and the contested ideas of un-Americanism and Americanism on the other. It is only within the context of that struggle over un-Americanism's evolving definition, it is argued, that the official decision of civil rights organizations such as COFO and SCLC – whose members had suffered personally from Klan violence – to oppose the proposed HUAC investigation of the Klan can be understood. Similarly, that ongoing contest explains how it was that, after almost three decades of investigating left-wing organizations that often included those fighting for greater civil rights, HUAC was finally moved to turn its attention to the right. Finally, this essay seeks to determine what it was, precisely, about the Klan in 1965 that was deemed "un-American" rather than simply criminal.